Yield and quality of winter wheat (Triticum aestivum L.) grain in relation to nitrogen fertilization - Yaroslav Tsvey (Revista Facultad Nacional de Agronomía - Medellín, 2021)
Winter wheat is commonly cultivated in Ukraine. This crop has nutritional requirements that have been affected due to the climate changes that in the recent years the country has been suffered. In the spring season, the plant is found in growing stage, which requires a suitable nitrogen nutrition and it must be supplied due to the deficit of this element during the vegetative development. Within this framework, this study aimed to establish the optimal nitrogen rate for winter wheat that was applied in different configurations on leached black soil, and to determine the effectiveness of nitrogen application to the frozen soil surface in early spring as a basis for these fertilizations. The experiment was conducted at the Bila Tserkva Research-Selection Station (Ukraine) during 2017-2019. The soil of this place corresponds to a leached loamy black soil (Mollisol) with content of organic matter between 3.6-3.8%, mobile phosphorus (P2O5) 156-166 mg kg-1, potassium (K2O) 64-77 mg kg-1, and pHKCl 5.8-6.3. A randomized experimental design with four nitrogen rates (0, 60, 80, 110 kg ha-1) with four replications as factorial arrangement was used. The results indicated that winter wheat yield was significantly affected by all nitrogen fertilizer rates (P<0.05). The highest average grain yield was obtained with 110 kg ha-1 nitrogen rate that combined application nitrogen to the frozen soil surface and the foliar feeding with 6.90 t ha-1. In years of regular precipitation during the growing season (2018-2019), nitrogen fertilizers had a more pronounced effect on winter wheat yield than in a year of precipitation deficiency (2017). A significant increase in grain protein content was obtained in variants where foliar feeding of winter wheat with urea solution was a part of fertilization strategy; it was attributed to nitrogen rates of 80 and 110 kg ha-1. The increase in protein content of the grain was less dependent on the weather conditions and was stable through the years of experiment.